Perbandingan Metode Barbeau Test dan Metode Pengamatan Klinis dalam Menilai Patensi Arteri Radialis Selama Kompresi pada Pasien Post Prosedur Kateterisasi Jantung di Ruang Angiografi Koroner dan Cardiac Intensive Care Unit RSUP. Dr. Hasan Sadikin Bandun - Nurhusna . (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2014)
ABSTRACT Background : Radial artery occlusion is one of the transradial vascular complications post cardiac catheterization. To minimize the effect of vascular problem related to local compression by using compression methods after cardiac catheterization would be decrease vascular complication such as radial artery occlusion (RAO). This research was conducted to determine the comparison between the Barbeau test method and the clinical observation method carried out by the researcher in order to examine the patency of radial artery during compression, post procedure cardiac catheterization at the Angiography Coroner Unit and the Cardiac Intensive Care Unit, Hasan Sadikin Bandung General Hospital, Indonesia. Methods : This research was a quantitative research using the comparative study design. The subjects of this research were 20 patients who took cardiac catheterization procedure using radial artery access site at the Angiography Coroner Unit and checked in pairs. The measurement was conducted gradually in three hours using compression band, namely the Stepty-P. The statistical test, specifically the McNemar test, was used to analyze the comparasion between the Barbeau test method and the clinical observation method, meanwhile the single variable data were analyzed by the distribution frequency. Result : According to the research result, it depicts that the distribution frequency of subjects who suffer from radial artery blood flow during compression period based on Barbeau Test at the first fifteen minutes were 7 patients (35%), the number of patients declined negligibly after 3 hours to 5 patients (25%), whereas the result from the clinical observation methods  was 1 patient (5%) at the first fifteen minutes, it then raise marginally after 3 hours to 2 patients (10%).  The statistical result shows that there wsere a significant difference in radial artery evaluation during compression period between two methods, in which at the first fifteen minutes (p=0,035) and the first thirty minutes (p=0,035), respectively, soon after the use of compression band, while overall, the statistical test result shows that there were no significant difference in comparison of two methods within the 45 minutes and 3 hours of compression periods (p>0.05). Conclusion : It is suggested to the nurse in the intensive care unit of cardiology to use the Barbeau Test method in assessing the patency of radial artery during compression period,  post procedure transradial cardiac catheterization.   Keywords : Barbeau test, clinical observation, radial artery, patency, cardiac catheterization.